Open Technical Writing An Open-Access Text for Instruction in Technical and Professional Writing - Pope, Adam Rex; Open Textbook Library (Open Textbook Library, 2018)
This book presents technical writing as an approach to researching and carrying out writing that centers on technical subject matter. Each and every chapter is devoted to helping students understand that good technical writing is situationally-aware and context-driven. Technical writing doesn't work off knowing the one true right way of doing things-there is no magic report template out there that will always work. Instead, the focus is on offering students a series of approaches they can use to map out their situations and do research accordingly.
What is Technical Writing? -- The User -- Visual Communication & Technical Writing -- Document Design in Technical Writing -- Writing in Genres -- Managing a Project -- Research Methods for Technical Writing
In English.
Description based on online resource
Keywords: Communication -- Textbooks